Back to the Future of qEEG: Lifespan Normative Modeling of Spectral Ratios and Functional Indices with Potential Applications to Therapeutic Monitoring - J. Bosch-Bayard; J. Guerrero-Sauzameda; R. I. Bosch-Bayard; R. Pérez-Elvira; A. Bosch-Castro; J. Sánchez-Rodríguez; A. Flores; K. Flores; E Resendiz-Flores; A. Ferrando; P. Ferrando; L. Galán-García; et al. (Brain Topography, 2026)
Quantitative EEG (qEEG) provides objective, millisecond-resolution measures of brain dynamics. Despite decades of methodological advances, clinically relevant derived indices—spectral power ratios, cognitive-emotional state markers, and physiological parameters—are typically reported as raw values without the normative context required for individualized clinical inference. To develop the first systematic age-dependent normative models for this family of derived qEEG indices using a multinational database, enabling probabilistic Z-score interpretation at the individual level with potential applications in objective therapeutic monitoring. Normative modeling was applied to the HarMNqEEG database ( n = 1,564 neurologically healthy participants, ages 5–97, 9 countries, eyes-closed resting state). Electrode-level Spectral Normalization (ESN) removed inter-individual and inter-device amplitude variability while preserving the neurophysiological interpretability of each index. Age-dependent normative trajectories were estimated using Generalized Additive Models for Location, Scale, and Shape (GAMLSS) with P-splines on log(age), allowing conditional mean and variance to vary non-linearly across the lifespan. GAMLSS modeling revealed significant non-linear age-dependent trajectories for all indices. Slow-wave-dominated ratios showed steep decreases from childhood to early adulthood, consistent with cortical maturation; alpha-dominated indices increased during adolescence before stabilizing. ESN normalization yielded well-calibrated normative residuals across the full age range for all indices, except Valence. For the Valence index, a quantile regression model is provided as the recommended normative reference due to its spike-and-slab marginal distribution. These normative models provide a principled, age-adjusted probabilistic framework for individual-level qEEG interpretation, based on eyes closed resting state recordings, laying the methodological groundwork for future clinical validation in diagnostic and therapeutic monitoring applications. The ESN strategy requires no knowledge of recording equipment, ensuring broad applicability across clinical and research settings.

Seed banking of mediterranean coastal plants: an analysis to identify current seed availability and gaps to guide future seed collection and habitat restoration activities - Marcello De Vitis; Valter Di Cecco; Mohamed Abdelaal; Gianluigi Bacchetta; Jože Bavcon; Kenza Saadiya Benmenni; Maurizio Bianchelli; Magda Bou Dagher Kharrat; Joseph A. Buhagiar; Francesca Carruggio; Angelino Carta; Simona Casavecchia; et al. (Journal of Coastal Conservation, 2025)

Current state of plant conservation translocations across Europe: motivations, challenges and outcomes - Sandrine Godefroid; Sam Lacquaye; Andreas Ensslin; Sarah Dalrymple; Thomas Abeli; Hannah Branwood; Inmaculada Ferrando Pardo; P. Pablo Ferrer Gallego; Elke Zippel; Luísa Gouveia; Carlos Alberto Lobo; Francisco Fernandes; et al. (Biodiversity and Conservation, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Extremophiles as Plant Probiotics to Promote Germination and Alleviate Salt Stress in Soybean - Ana P. Santos; Carolina Belfiore; Cristina Úrbez; Alejandro Ferrando; Miguel A. Blázquez; María E. Farías (Journal of Plant Growth Regulation, 2023)

Fields with no recent legume cultivation have sufficient nitrogen-fixing rhizobia for crops of faba bean (Vicia faba L.) - Marta Maluk; Francesc Ferrando-Molina; Laura Lopez del Egido; Adrian Langarica-Fuentes; Genet Gebre Yohannes; Mark W. Young; Peter Martin; Richard Gantlett; Greg Kenicer; Cathy Hawes; Graham S. Begg; Richard S. Quilliam; et al. (Plant and Soil, 2022)
Purpose (1) To assess the biological N fixation (BNF) potential of varieties of faba bean ( Vicia faba L.) cropped with or without compost in an experimental field-scale rotation with no recent history of legumes, (2) to enumerate soil populations of Rhizobium leguminosarum sv. viciae ( Rlv ), and to genetically characterize the nodulating Rlv strains, (3) compare BNF with other sites in Britain. Methods BNF was evaluated from 2012 to 2015 using 15 N natural abundance. Treatments were either PK fertilizer or compost. Soil rhizobial populations were determined using qPCR, the symbiotic rhizobia genotyped (16 S rRNA, nodA and nodD genes), and their BNF capacity assessed ex situ . The reliance of legumes on BNF at other British sites was estimated in a single season, and their nodulating symbionts examined. Results Faba bean obtained most of its N through BNF (>80%) regardless of variety or year. N-accumulation by cvs Babylon and Boxer increased with compost treatment in 2014/2015. Rhizobial populations were c. 10 5 -10 6 Rlv cells g −1 soil regardless of field or treatment. 157 Rlv microsymbionts grouped into two large nodAD clades; one mainly from V. faba , and the other from various legumes. All isolates nodulated, and some performed better than commercial inoculant strains. Conclusions Faba bean can provide most of its nitrogen through BNF and leave economically valuable residual N for subsequent crops. Recent legume cropping in northern Europe is not essential for effective nodulation: rhizobia may persist in a range of farmland locations. Nevertheless, there is the potential to apply elite rhizobial strains as inoculants in some soils.

Determination of probabilities for the generation of high-discharge flows in the middle basin of Elqui River, Chile - Iván P. Vergara Dal Pont; Fernanda A. Santibañez Ossa; Diego Araneo; Francisco J. Ferrando Acuña; Stella M. Moreiras (Natural Hazards, 2018)

Microorganisms reveal what plants do not: wheat growth and rhizosphere microbial communities after Azospirillum brasilense inoculation and nitrogen fertilization under field conditions - Luciana P. Di Salvo; Lucía Ferrando; Ana Fernández-Scavino; Inés E. García de Salamone (Plant and Soil, 2018)

Translocation of Limonium perplexum (Plumbaginaceae), a threatened coastal endemic - Emilio Laguna; Albert Navarro; Patricia Pérez-Rovira; Inmaculada Ferrando; P. Pablo Ferrer-Gallego (Plant Ecology, 2016)

Taxonomic and Functional Resilience of Grasshoppers (Orthoptera, Caelifera) to Fire in South Brazilian Grasslands - C P R Ferrando; L R Podgaiski; M K M Costa; M D S Mendonça (Neotropical Entomology, 2016)

Fragments of the Western Alpine Chain as Historic Ornamental Stones in Turin (Italy): Enhancement of Urban Geological Heritage through Geotourism - A. Borghi; A. d’Atri; L. Martire; D. Castelli; E. Costa; G. Dino; S. E. Favero Longo; S. Ferrando; L. M. Gallo; M. Giardino; C. Groppo; R. Piervittori; et al. (Geoheritage, 2014)

Melanism in the gastric mucosa of the scalloped ribbonfish from the Ligurian Sea - M. Bottaro; S. Ferrando; T. Ferrando; P. N. Psomadakis; M. Vacchi (Journal of Fish Biology, 2005)
Internal stomach melanism was observed in two scalloped ribbonfish Zu cristatus from the Ligurian Sea. The phenomenon may help prevent advertizing the presence of this species after consumption of bioluminescent prey.

Setting up a PCR Based Method to Trace Animal Species in Processed Meat Products - M.N. Losio; M.L. Ferrando; P. Daminelli; F. Chegdani (Veterinary Research Communications, 2004)